2014
DOI: 10.1002/wcc.273
|View full text |Cite
|
Sign up to set email alerts
|

The potential of microblogs for the study of public perceptions of climate change

Abstract: Microblogs are electronic platforms that convey brief communications posted by users. Keyword searches in popular microblogs, like Twitter, reveal fragments of users' knowledge of and views on issues like climate change. Evaluations of climate change communications in the microblogosphere are rare even compared with the few studies on the impacts of Web sites and blogs on users' perceptions of climate change. However, extant research focuses more often on appraising logic and evidence in microblog discourse th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 29 publications
0
31
0
2
Order By: Relevance
“…Although scholars have recently begun to characterize the effects of certain forms of new media on public engagement with climate change, such as partisan news and political comedy (Feldman, Leiserowitz, & Maibach, 2011;Feldman, Maibach, RoserRenouf, & Leiserowitz, 2012;Hmielowski, Feldman, Myers, Leiserowitz, & Maibach, 2014), few studies have examined the role of social media in fostering engagement with climate and energy issues (Auer, Zhang, & Lee, 2014;Baym & Shah, 2011). Yet these social connections matter: Rolfe-Redding, Maibach, found that Republicans who reported greater levels of activity within their social network to reduce climate change also reported greater levels of belief in climate change and support for mitigation policies.…”
Section: Republicans' Views Of Climate Change and Energy Policymentioning
confidence: 98%
“…Although scholars have recently begun to characterize the effects of certain forms of new media on public engagement with climate change, such as partisan news and political comedy (Feldman, Leiserowitz, & Maibach, 2011;Feldman, Maibach, RoserRenouf, & Leiserowitz, 2012;Hmielowski, Feldman, Myers, Leiserowitz, & Maibach, 2014), few studies have examined the role of social media in fostering engagement with climate and energy issues (Auer, Zhang, & Lee, 2014;Baym & Shah, 2011). Yet these social connections matter: Rolfe-Redding, Maibach, found that Republicans who reported greater levels of activity within their social network to reduce climate change also reported greater levels of belief in climate change and support for mitigation policies.…”
Section: Republicans' Views Of Climate Change and Energy Policymentioning
confidence: 98%
“…To date there has been little study of social media discourse or online social networks relating to the important and contentious topic of climate change (Schafer, 2012;Auer et al, 2014). Recent studies have looked at social media discussions around the September 2013 release of the IPCC Fifth Assessment Report (Pearce et al, 2014), at framing of the IPCC reports in legacy and social media (O'Neill et al, 2015), at interconnections between climate sceptic blogs (Sharman, 2014), and at the overall volume of activity and common topics of climate-related discussion worldwide (Kirilenko and Stepchenkova, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Such apparent uncertainty may weaken support for political action on strategies of mitigation or adaptation. While broadcast and print media presentation of climate-related issues plays an important role in shaping public opinion (Carvalho, 2010;Moser, 2010), understanding how climate change is presented and discussed online is rapidly becoming an area of central importance (Schafer, 2012;Auer et al, 2014). Social media are already an important locus for information exchange, debate, and opinion formation on a range of issues, including climate change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A investigação sobre as mudanças climáticas nas redes sociais é recente e ainda limitada, apesar do potencial e do vasto campo de informação que as redes sociais proporcionam (O'Neill & Boykoff, 2011;Auer et al, 2014). Sabe-se que a realização de eventos internacionais, as agendas intergovernamentais, as publicações de lideranças políticas e/ou pessoas famosas e os eventos meteorológicos extremos proporcionam um aumento nas abordagens não só na mídia tradicional como também nas referências ao tema nas redes sociais (Kirilenko & Stepchenkova, 2014;Pearce et al, 2014;Cody et al, 2015).…”
Section: Breve Revisão Da Literaturaunclassified